Japan's Experience with Deposit Insurance and Failing Banks: Implications for Financial Regulatory Design? - Curtis J. Milhaupt (Washington University Law Quarterly, 1999)
This Article examines three decades of Japanese experience with deposit insurance and failing banks, and analyzes the implications of that experience for bank safety net reform in other countries.
Keywords: Deposit insurance – Japan; Bank failures; Banking law; Financial services